Development of filter media from cellulose acetate polymer containing silver nitrate (AgNO3) - Zamanikia, Ali (2024)
This master's thesis provides a thorough analysis of the creation of nanofiber media with enhanced antibacterial characteristics that are integrated with cellulose acetate polymer and silver nitrate (AgNO3). The study focuses on the synthesis and characterization of electrospun nanofibers, employing a range of analytical techniques, including Fourier Transform Infrared Spectroscopy (FT-IR), filter efficiency, and filter permeability. The primary objective of this research is to understand the influence of varying silver nitrate concentrations (3%, 5%, and 10%) on the properties of cellulose acetate nanofibers. Scanning Electron Microscopy (SEM) analysis reveals that the nanofiber diameter is affected by the addition of silver nitrate, with preliminary findings indicating that higher concentrations result in decreased nanofiber diameter compared to lower concentrations or pure cellulose acetate nanofibers. This observation suggests the potential for tuning nanofiber properties to achieve specific filtration and antibacterial performance. Furthermore, the study investigates the chemical composition and bonding modifications within the cellulose acetate nanofibers. FT-IR spectroscopy reveals spectral changes associated with the incorporation of silver nitrate at different concentrations, indicating possible modifications in chemical composition and bonding. These modifications are suggestive of interactions between silver nitrate and the cellulose acetate polymer, which alter the molecular structure and functional groups within the nanofibers. Also, the permeability and efficiency results provide valuable insights into the impact of silver nitrate concentration on the filter's performance. The findings of this research offer valuable insights into the development of filter media with tailored antibacterial properties, highlighting the potential for optimizing nanofiber diameter and chemical composition through the controlled addition of silver nitrate.